2016
DOI: 10.1039/c5fo00624d
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents cisplatin-induced decrease in the tight and adherens junctions: relation to oxidative stress

Abstract: Curcumin is a polyphenol and cisplatin is an antineoplastic agent that induces nephrotoxicity associated with oxidative stress, apoptosis, fibrosis and decrease in renal tight junction (TJ) proteins. The potential effect of curcumin against alterations in TJ structure and function has not been evaluated in cisplatin-induced nephrotoxicity. The present study explored whether curcumin is able to prevent the cisplatin-induced fibrosis and decreased expression of the TJ and adherens junction (AJ) proteins occludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…Previous studies have demonstrated that curcumin suppresses cytotoxicity and DNA injury by suppressing oxidative damage caused by reactive oxygen species (27,28). The current study observed that curcumin decreased the viability of human lung cancer cells in an apparent dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have demonstrated that curcumin suppresses cytotoxicity and DNA injury by suppressing oxidative damage caused by reactive oxygen species (27,28). The current study observed that curcumin decreased the viability of human lung cancer cells in an apparent dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, curcumin is the main active compound of Curcuma longa L. and is considered a bifunctional antioxidant, its consumption, in both animals and humans, has been recognized as safe by the Food and Drug Administration . Curcumin is an effective ROS scavenger; it is able to scavenge superoxide anion ( O2), singlet oxygen, hydrogen peroxide (H 2 O 2 ), peroxynitrite anion, hypochlorous acid, hydroxyl radicals, and peroxyl radicals . Curcumin has been reported to prevent oxidative stress and renal damage induced by chemicals like gentamicin , cisplatin and maleate .…”
Section: Introductionmentioning
confidence: 99%
“…In our group we also found that curcumin could inhibit the occurrence of EMT in renal tubular epithelial cells via regulating several sites of the TGF- β /Smads signal transduction pathway in UUO rats [49]. The inhibitory effect of curcumin on EMT was also demonstrated in cisplatin-induced renal fibrosis rats [31]. …”
Section: Curcumin Is Also Actively Involved In Activation Stage Ofmentioning
confidence: 96%
“…The protective effect of curcumin was more obvious in pretreatment group (administration of curcumin before selenium, 24 h) than simultaneous or posttreatment group (administration of curcumin after selenium treatment, 24 h). In rats with contrast-induced nephropathy [30], 5/6 Nx [24], and cisplatin-induced nephrotoxicity [31], curcumin treatment (60 and 120 mg/kg for 60 days [24]) increased antioxidant profiles (e.g., superoxide dismutase (SOD), enzymes catalase, glutathione reductase, glutathione peroxidase, and glutathione) and decreased oxidant profile (malondialdehyde) in the kidneys. Further, curcumin may exhibit renoprotective effect through Nrf2 translocation [31, 53], which beneficially contributes to ameliorating cisplatin-induced loss of tight junction proteins (claudin-2 and occludin) and adherens junction protein (E-cadherin and β -catenin) [31].…”
Section: Curcumin Is Also Actively Involved In Activation Stage Ofmentioning
confidence: 99%
See 1 more Smart Citation